The Influence of Profitability, Transfer Pricing, Capital Intensity, Independent Commissioners, and Audit Committee on Tax Avoidance (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019 – 2024) - Perdana, Yoean Octarhaiezky; Akbar, Taufik (Baca Dulu Publisher, 2025)
This study aims to examine and analyze the effect of profitability, transfer pricing, capital intensity, independent commissioners, and the audit committee on tax avoidance on manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2024. This is a quantitative research study. The population for this research consists of manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2024. The sample was determined using a purposive sampling method, resulting in 34 companies that met the specified criteria. The study utilized secondary data sourced from the Indonesia Stock Exchange website. Data processing and analysis were conducted using Eviews 13, with a panel data regression model as the analytical method. The results show that profitability has no effect on tax avoidance, transfer pricing has no effect on tax avoidance, capital intensity has an effect on tax avoidance, independent commissioners have no effect on tax avoidance, and the audit committee has no effect on tax avoidance.